Microanomia e valores humanos: contribuições para compreensão do comportamento antissocial - Lopes, Guilherme Sobreira (2015)
Anomie is a condition of the social structure characterized by the absence or weakening of social norms. At the individual level, is the state of decompensation or imbalance on the prioritization of personal values front to social values. In this sense, a psychological construct appears to be particularly associated with anomie: human values. This dissertation aimed to evaluate the value basis of anomie and its relations with antisocial behavior. Therefore, two studies were performed. Study I aimed to evaluate the relationship between value decompensation between low congruence values and demographics. Participated of this study 1147 students of primary and secondary school and college city of João Pessoa - PB, aged between 10 to 45 years (m = 16.1, SD = 4.5, and 64.8% between 11 and 17 years ) with majority women (60.1%), Catholic (60.6%) and from public schools (52.1%). They answered the Basic Values Questionnaire - QVB and demographic issues. The application of the instruments occurred in schools and universities. The results indicated that microanomie does not depend of social class, but varies according to gender and age group. Study II aimed to test the hypothesis of consistency and compatibility of human values and evaluate the microanomie in samples of general population and imprisoned. To do so, two samples were considered. The first included 994 individuals from the general population, aged between 14 to 56 years (m = 21.7, SD = 6.3, and 49.8% between 18 and 25 years), mostly female (50.6%), heterosexual (87.6%) and Catholic (49.5%). The second included 762 prisoners aged between 19 to 66 years (m = 29.6, SD = 8.5, and 49.5% between 19 and 27 years), predominantly male (71.9%), heterosexual (87 7%) and Catholic (42.1%). The first sample responded to the QVB and demographic issues. The sample of incarcerated answered the QVB and 73 items that addressed different facets of their lives, namely: prison history, educational profile, employment profile, family structure, experiences in the prison system, mental health indicators and demographic questions. The results confirmed the hypothesis of consistency and compatibility. On the other hand, the assumptions related to the comparison of microanomie levels in the general population and prisoners were refuted. This study brings contributions to the understanding of antisocial behavior and to the development of theoretical models.